“My Future”: A Qualitative Examination of Hope in the Lives of Black Emerging Adults - William Terrell Danley; Benson Cooke; Nathalie Mizelle (Social Sciences, 2025)
The presence of hope significantly influences how youth interpret possibilities and commit to future-oriented action. This qualitative study investigates how fifteen Black emerging adults, ages eighteen to twenty-five, living in a major United States urban city on the East Coast, describe their aspirations, goal-setting strategies, and responses to personal and structural challenges. Participants were categorized as connected or disconnected based on their engagement in school, work, or training programs. Using Reflexive Thematic Analysis of interviews, the research identified key differences in agency, emotional orientation, and access to guidance between the two groups. Connected participants often described clear, structured goals supported by networks of mentorship and opportunity. Disconnected participants expressed meaningful hope, yet described fewer supports and greater uncertainty in achieving their goals. These findings highlight how consistent exposure to guidance and structured environments strengthens future orientation and internal motivation. These results deepen our understanding of how young people experience hope across diverse contexts and show that mentorship, intentional goal setting, and greater access to opportunity play a vital role in sustaining hopeful thinking during the transition to adulthood.